Impact of delignification on mechanical, morphological, and thermal properties of wood sawdust reinforced unsaturated polyester composites - Md Rezaur, Rahman; Md Mizanur, Rahman; Sinin, Hamdan; Josephine, Chang Hui Lai (Society of Plastics Engineers (SPE), 2016)
Mechanical, morphological, and thermal properties of the raw and delignified wood sawdust (DWS) reinforced unsaturated polyester (UP) composites were evaluated. Composites were prepared using Resin Transfer molding technique by changing filler loading (5, 10, 15, and 20 wt%) for both raw and DWS reinforced UP. Mechanical (tensile and flexural), Fourier transform infrared spectroscopy (FTIR), morphological (scanning electron microscopy [SEM]) and thermal (thermogravimetric analysis [TGA]) properties were successively characterized. FTIR confirmed the removal of lignin from wood sawdust during the delignification process. The tensile strength, Young's modulus, and flexural strength values increased only up to 15% filler loading then decreased with increasing the filler. DWS reinforced composites had better mechanical properties compared to raw composites. SEM micrographs reveal that DWS reinforced composites have good compatibility with UP resin. According to TGA results, DWS reinforced composites showed enhanced thermal stability at the final decomposition stage above 400°C.